The satellite chlorophyll signature of Lagrangian eddy trapping varies regionally and seasonally within a subtropical gyre - A. E. Jones-Kellett; A. E. Jones-Kellett; M. J. Follows (Ocean Science, 2025)
Vertical motions of mesoscale ocean eddies modulate the resource environment, productivity, and phytoplankton biomass in the ocean's subtropical gyres. The horizontal circulations can trap or disperse the eddy-driven chlorophyll anomalies, which can be observed from space. From 2 decades of satellite remote sensing observations in the North Pacific Subtropical Gyre (NPSG), we compared the chlorophyll anomalies within “leaky” eddy boundaries identified using an Eulerian sea level anomaly (SLA) method and within strictly coherent “trapping” bounds derived from Lagrangian particle simulations. On average, NPSG Lagrangian coherent vortices maintain stronger chlorophyll anomalies than Eulerian SLA eddies due to the limitation of lateral dilution. This is observed in both cyclones and anticyclones. However, there is variability in the biological signature of trapping by sub-region and season. Eddy trapping of positive chlorophyll anomalies is most significant in the southern regions of the NPSG, counter to expectations from a commonly used Eulerian metric of eddy trapping. We found weak relationships between eddy age and the magnitude of surface chlorophyll anomalies in most long-lived Lagrangian coherent vortices; the strongest exception was in wintertime anticyclones in the lee of the Hawaiian Islands, where chlorophyll increases throughout eddy lifetimes. Overall, our results challenge the assumption that Eulerian-identified mesoscale eddy boundaries are coherent and suggest that Lagrangian trapping, combined with regional and seasonal factors, shapes the chlorophyll concentrations of subtropical mesoscale eddies.